A fluorescent molecular capsule with a flexible polyaromatic shell for the detection of monoterpene compounds in water. Issue 15 (25th January 2016) - Suzuki, Akira; Kondo, Kei; Sei, Yoshihisa; Akita, Munetaka; Yoshizawa, Michito
Abstract : A new molecular capsule composed of U-shaped polyaromatic amphiphiles was synthesized and acts as a fluorescent supramolecular probe for recognizing various monoterpenes in water. Abstract : A new molecular capsule with a flexible fluorescent shell was formed by the quantitative self-complementary assembly of amphiphilic, U-shaped polyaromatic subunits in water. The capsule can fully encapsulate a variety of non-fluorescent monoterpene compounds ( e.g., menthone, menthol, and p -menthane) in the hydrophobic cavity and act as a fluorescent supramolecular probe for recognizing the structural identity of the analytes by emissive signals in water at room temperature.